KEMAJEMUKAN DALAM PERSPEKTIF ORANG ALOR DIASPORA: KAJIAN SOSIOLOGIS TERHADAP TARA MITI TOMI NUKU - Pellondou, Andri Oktovianus (Lembaga Berugak Baca, 2024)
This study aims to examine the perspective of the Alor diaspora in Kupang regarding diversity. The framework of this study is based on their outlook on life which is manifested in the motto Tara Miti Tomi Nuku. The researcher will examine their perspective in terms of ontology, epistemology, and axiology. After that, the researcher also examines it sociologically using the theory of Structural functionalism. The researcher chose this study because no one has studied it. Many have studied Alor but no one has studied the perspective of the Alor diaspora. The method used in this study is a qualitative method. The contribution of this study is to provide ideas or concepts for science and to contribute to Indonesian society to appreciate how to live in diversity